Effectiveness of Online Film Posters on Students’ Achievement in Writing Descriptive Text - Rahmawati, Wiki Tedi (Universitas Pendidikan Mandalika, 2022)
This research aimed to determine whether the online film posters as a teaching medium significantly affected students’ achievement in writing descriptive text. This research was conducted using a quasi experimental research with pre-test and post-test design. The population was 60 students of the tenth grade senior high school of MAS Muhammadiyah 13 Sei Rampah, Medan. There were two parallel classes as the population, namely Class X IPA and X IPS. Each class consisted of 30 students. The sample in this research was taken using the cluster sampling technique to decide the experimental and control groups. X IPA was the experimental group and X IPS was the control group. The experimental group consisted of 30 students was taught using online film posters and the control group consisted of 30 students was taught without using any media. There were five meetings during the research. The first and the fifth meetings were administered as pre-test and post-test while the other three meetings were administered as the treatment sessions.The instrument used to collect the data was a writing test. The students of both groups were assigned to write a descriptive text to be administered as the research data. It was obtained that the mean score of experimental group in pre-test was 74.86 and 79.93 in post-test while the mean score of control group in pre-test was 73.66 and 69.9 in post-test respectively. These statistical data were then analyzed using t-test formula. The result of t-test calculation showed the value of t-observed was 3.20 and the value of t-table was 2.00 in level of significance of 0.05 and df=58. This meant that t-observed was higher than t-table (3.20 > 2.00). Based on the finding, then alternative hypothesis (Ha) was accepted and null alternative (Ho) was rejected. Thus, it was concluded that online film posters significantly affected students’ achievement in writing descriptive text.